Exploring gendered racism and the mental health of rural Black women - Ezemenaka, Christina J.; Burton, Wanda Martin; Newman, Sharlene (Frontiers in Public Health, 2025)
BackgroundGendered racial microaggressions adversely impact Black college women’s mental health, but less is known about rural Black women’s mental health.ObjectiveExamine the association between gendered racism, depression, and psychological distress.MethodsThis cross-sectional study included 200 rural Black women from the Southeastern United States. Gendered racism was assessed using the Gendered Racial Microaggressions scale (GRMS). Linear regression was used to assess GRM subscales, depression (PHQ-9) and psychological distress (K6) as outcomes.ResultsOf the 200, 21.5% reported depression and 31% reported moderate psychological distress. Depression increased with increasing stress appraisal of gendered racism, p = 0.002.ConclusionGendered racial microaggressions impact the mental health of rural Black women.